Determination of fingernail chromium, cadmium, and lead in tannery workers - Liao, Yen-Hsiung (International Journal of Health, 2015)
Purpose: To determine whether chromium, cadmium, and lead levels in human Fingernails reflected the exposure to workplace contamination in tanneries.Approach: 49 exposed tanning workers and 33 controls were monitored for fingernail levels of chromium, cadmium, and lead by graphite furnace and hydride atomic absorption spectroscopy.Results: The mean levels of fingernail chromium, cadmium, and lead in the exposed workers were significantly higher than those in the controls. In regression models for the tannery workers, the significant risk factor that affected the fingernail chromium, Cadmium, and lead level were occupational exposure, respectively. Current smoker it showed a significant change in trend of increased fingernail cadmium levels.Conclusion: These findings indicate that chromium, cadmium, and lead absorbed from. Leather tanning compounds result in raised levels of chromium, cadmium, and lead in fingernails and that improvement of the industrial health should be more practiced in the tanneries in Taiwan.